Tally-based thresholds as an alternative to density-based thresholds for sugarcane aphid, Melanaphis sacchari, (Hemiptera: Aphididae) in grain sorghum. (October 2021) - Gordy, John W.; Way, M.O.; Bowling, Robert D.; Brewer, Michael J.
Abstract: Sugarcane aphid, Melanaphis sacchari Zehtner (Hemiptera: Aphididiae), has become a major pest of grain sorghum, Sorghum bicolor (L.) Moench, in North America since being detected in 2013. A density-based economic threshold of 40 aphids per leaf has been established for hybrids susceptible to the aphid. Direct counts of aphids are needed for use of density-based thresholds, but the counts are time-consuming and may rely on estimation of numbers of aphids in clusters which may vary in accuracy. Therefore, a tally-based threshold was considered by evaluating the aphid infestation proportion – aphid density relationship for three selected tallies, validating the tally-based approach in decision-making, and comparing time efficiency of the two approaches. Using data collected at three Texas locations from 2015 to 2018, linear and polynomial regressions for tallies of >25, >50, and >100 aphids per leaf were related to aphid densities, with polynomial regressions providing the best fit. Solving the equations, tally threshold proportions of 0.23, 0.16, and 0.11 using a tally of >25, >50, and >100 aphids per leaf, respectively, were equivalent to a density-based threshold of 40 aphids per leaf. In a validation exercise using 50 and 100 aphids per leaf tally thresholds and a fixed sample size of 100 leaves from five commercial grain sorghum fields of varying aphid density, the tally threshold infestation proportion derived from the polynomial regressions produced the same management decision in all cases. Additionally, the tally-based threshold approach was more time efficient than the density-based approach, requiring half the time to sample 100 leaves. Highlights: Tally-based thresholds provide the same treatment decision as density-based thresholds. Polynomial models provide a better estimation of tally-based aphid infestation proportion, compared to linear models. Tally-based threshold provides a 50% time savings over density-based approach.